Writing Research Articles for Academic Journals: A Guide for Novice Researchers (SNPRC Journal, 2024)
Research articles are essential outputs of academic work. They represent intensive and detailed studies on specific topics or issues within a particular academic discipline. Usually grounded in primary data, they offer structured, evidence-driven insights that help expand current knowledge or introduce new viewpoints. Research articles are commonly structured using the IMRD format: Introduction, Method, Results, and Discussion which ensures clarity, coherence, and scientific rigor. The purpose of writing such articles is not only to share findings with the academic community but also to stimulate further research and critical discussion. For emerging scholars, a clear understanding of the research article writing process is essential. Nevertheless, many novice researchers often experience confusion and face challenges when attempting to write and publish their work in academic journals. In this light, the present study aims to examine both the theoretical and practical aspects of research articles, along with their types. Moreover, it discusses the fundamental elements of a research article, supported by relevant examples and illustrative explanations.